Local actors and service delivery in fragile situations - Peter Albrecht (Danish Institute for International Studies (DIIS), 2013)
This report explores how to engage local actors in international development programming that aims to strengthen service delivery in fragile situations. Apart from a discussion of how policy-makers and practitioners should approach local actors and centrally governed institutions systemically, three case studies are presented. They explore different types of external support, and the effect it has had, exploring community policing in Sierra Leone, primary healthcare by village doctors in Bangladesh, and primary education provided by non-governmental or - ganizations (NGOs), traditional voluntary organizations and madrasas - religious seminaries - in Pakistan. The report puts forward two interrelated arguments. First, the quantity and quality of service provision in fragile situations cannot simply be equated with a set of centrally governed institutions. Service delivery in fragile situations is performed by a broad range of actors, including, but not limited to, NGOs, grass-roots organizations and community-based organizations, faith-based organizations, traditional voluntary organizations, customary organizations (chiefs and tribal leaders), and religious leaders. ...
Keywords: 300